RITE CHACHYLGA: MODERN FUNERAL AND MEMORIAL RITES IN THE TRADITIONAL CULTURE OF ALTAI - Тадышева, Н. О. (Journal of history, 2018)
Funeral and commemoration ritual is considered to be one of the most conservative and ethnically indicative spheres of traditional culture. Field materials show that unlike the maternity and wedding, the traditional burial rites of the Altai population of the Altai Republic have undergone the least changes, therefore archaic traits are preserved in them: animistic and totemic ideas. Today, the task of describing the complex of funeral-memorial ritual is not put. The article deals with the ritual of “chachylga” as a rite of passage. The study shows that in the traditional picture of the world of the Altai population, the visible and invisible life forms are one, but the events of the visible world (being) at every single moment depend on the forces of the invisible world (other-being). Clear regulation and mandatory observance of the ritual of “chachylga” in the modern funeral-memorial rites testifies to its sacredness. The notion that if the funeral rites were not fulfilled on death, the deceased is doomed to a miserable existence – he can not penetrate into the world of the dead and join the community that has formed there, nor remain in the world of the living. And that the deceased was included in the world of ancestors, the rites of transition are carried out – separation and inclusion, in order to preserve the continuity of generations.